Aluminum current collector for negative-electrode-free sodium metal battery and preparation method of aluminum current collector

By using fluorine-containing sulfonic acid-containing organic ligand solution on the surface of the aluminum current collector, a uniform fluorine-sulfonic acid-based anionic ligand layer is formed, which solves the battery instability problem caused by the damage of the oxide layer in the negative-electrode sodium metal battery, and achieves higher cycle stability and lower preparation costs.

CN120261590APending Publication Date: 2025-07-04XIAMEN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510453532.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

In existing negative-electrode-free sodium metal batteries, the dense oxide layer on the surface of the aluminum current collector will undergo an irreversible chemical reaction in the sodium-electrode potential interval, resulting in the destruction of the aluminum surface layer, triggering the accumulation of by-products, increasing the interface impedance and promoting the growth of sodium dendrites, affecting the stability of the battery cycle.

Method used

Fluorosulfonic acid-containing organic ligands are used as modification solutions, and a uniform fluorosulfonic acid-based anionic ligand layer is formed on the surface of the aluminum current collector through a simple water bath treatment, which improves the sodium sulfonic metallicity on the aluminum surface and promotes the uniform deposition of sodium metal.

Benefits of technology

The cycle stability of the negative electrode-free sodium metal battery is improved, the preparation cost is reduced, and the efficient modification of aluminum current collector is achieved through a simple processing process, the sodium-philic metal crystal surface of the aluminum foil is enhanced, and the long cycle performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120261590A_ABST
    Figure CN120261590A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum current collector for a negative-electrode-free sodium metal battery and a preparation method of the aluminum current collector. The method comprises the following steps: (1) respectively cleaning an aluminum foil in water and an ethanol solution to obtain a sample A with a clean surface; (2) annealing the sample A to obtain a sample B which is rich in a sodium-philic metal crystal face and has a uniformly oxidized surface; (3) treating the sample B in a pretreatment surface passivation solution to obtain a sample C; and (4) placing the sample C in an aqueous solution containing fluorosulfonic acid organic ligands, and carrying out water bath treatment to obtain the surface modified aluminum current collector rich in fluorosulfonic acid anion ligands. The crystal face on the surface of the aluminum current collector is changed to generate more hydrophilic metal interfaces; the surface modification of the aluminum current collector is realized through interface ligand exchange by using a fluorine-containing sulfonic acid organic ligand aqueous solution; the electrochemical stability of the aluminum current collector is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and particularly to an aluminum current collector for an anode-free sodium metal battery and a preparation method thereof. Background Art

[0002] With the increasingly serious global population problem, deteriorating environmental problems, and increasingly obvious energy problems, human society has begun to vigorously develop a new energy system for clean and sustainable development. The anode-free sodium metal battery has a higher battery energy density, a simpler preparation process, and a lower preparation cost because it completely replaces the excessive carbon layer or sodium metal on the negative electrode side with a simple current collector. These advantages make the anode-free sodium metal battery show great application potential in the field of consumer electronic devices.

[0003] In order to achieve stable cycling of the anode-free sodium metal battery, it is necessary to induce uniform deposition of sodium metal on the negative electrode side and generate a more stable SEI interface (solid electrolyte interface) to prevent excessive consumption of limited sodium metal. Based on this, researchers have modified the current collector by introducing sodiumophilic metal sites on the surface of the current collector and constructing a three-dimensional current collector. Wang et al. (Tianshi Wang, Yongchang Liu, et al. Energy Storage Mater. 2018, 15, 274-281.) in-situ constructed a uniform copper oxide nanowire modification layer on the surface of the copper foil to provide abundant sodium metal nucleation sites and promote the stable growth of sodium metal. Wu et al. (Wu Yang, Wang Yang, et al. Nano Energy, 2021, 80, 2211-2855.) deposited a uniform zinc oxide nanorod array on the surface of the copper foam by simple chemical deposition to construct a three-dimensional interface layer, while introducing more sodiumophilic metal sites while evenly distributing the charge. Effectively realizing the uniform deposition of induced sodium metal and greatly improving the battery cycling stability.

[0004] However, the above methods have complex pretreatment processes, and the mass density of the copper current collector itself (8.96 g / cm 3 ) and the preparation cost are relatively high, which is not conducive to further developing the energy density and preparation cost advantages of the anode-free sodium metal battery. In contrast, the aluminum current collector has a lower mass density (2.7 g / cm 3) and lower preparation costs. However, the dense oxide layer on the aluminum surface will undergo irreversible chemical reactions in the sodium metal negative electrode potential range (-2.71V vs SHE), resulting in the destruction of the aluminum surface layer and triggering the corrosion of the aluminum substrate. With the continuous accumulation of by-products, the interfacial impedance surges, ultimately leading to a series of problems such as the growth of sodium dendrites and capacity decay, and battery short circuit. Therefore, designing and developing a negative electrode aluminum current collector that can stabilize the sodium metal deposition interface and improve the cycle stability of sodium-free metal batteries is one of the most promising issues in the research of sodium-free metal batteries. Therefore, developing a simple and efficient strategy to improve the cycle stability of sodium-free metal batteries without a negative electrode to design and synthesize an aluminum negative electrode current collector is of great significance for the development of high-performance sodium-free metal batteries. Summary of the Invention

[0005] The purpose of the present invention is to provide a preparation method for a negative electrode current collector of a sodium-free metal battery with a simple process and low cost to solve one of the problems affecting the cycle stability of the battery, such as the unstable interface on the negative electrode side of the sodium-free metal battery, excessive side reactions leading to the growth of sodium metal dendrites, and the accumulation of "dead sodium".

[0006] The technical solutions adopted by the present invention to achieve the above purposes are as follows:

[0007] A preparation method for an aluminum current collector for an aluminum used in a sodium-free metal battery, comprising the following steps:

[0008] (1) Place the aluminum foil in deionized water and anhydrous ethanol for cleaning respectively to obtain a sample A with a clean surface. The ultrasonic washing time is preferably 10 - 30s.

[0009] (2) After drying the sample A, perform annealing treatment to obtain a sample B with a sodium-rich metal crystal plane and a uniformly oxidized surface. The annealing is preferably carried out in a porcelain boat and annealed at 100 - 600°C in an air atmosphere for 10 - 60 minutes. After cooling to room temperature, wash and dry to obtain the sample B.

[0010] (3) Place the sample B in a pre-treatment surface passivation solution to obtain a sample C. It is preferably soaked in the pre-treatment passivation solution at 30 - 50°C for 30s - 10 minutes, then quickly rinsed with deionized water and dried for standby.

[0011] (4) Place the sample C in an aqueous solution containing a fluorosulfonic acid-based organic ligand, and obtain a surface-modified aluminum current collector rich in fluorosulfonic acid-based organic ligand anions through a water bath treatment; the concentration of the aqueous solution containing the fluorosulfonic acid-based organic ligand is 0.1 - 0.5M; the water bath treatment temperature is 40 - 60°C, and the treatment time is 1 - 3h. After washing and drying, the aluminum current collector for the sodium-free metal battery is obtained.

[0012] Preferably, after water bath, it is cooled to room temperature, then washed 3-5 times with deionized water and dried to obtain the aluminum current collector.

[0013] Preferably, in the step (1), the aluminum foil is at least one of battery-grade commercial aluminum foils such as single-sided polished aluminum foil, double-sided polished aluminum foil, and microporous aluminum foil. Its thickness is preferably 15-20 μm.

[0014] Preferably, in the step (2), the rate of heating the aluminum foil from room temperature to 100-600 °C is 2-15 °C / min; the cooling from 100-600 °C to room temperature is natural cooling.

[0015] Preferably, the pretreatment passivation solution in the step (3) is one or more of an aqueous sodium oxide solution, ammonia water, an aqueous sodium carbonate solution, and an aqueous sodium bicarbonate solution.

[0016] Preferably, the concentration of the pretreatment passivation solution in the step (3) is 0.1-0.5 M.

[0017] Preferably, the aqueous solution of the fluorosulfonic acid-based organic ligand in the step (4) is an aqueous solution of a fluorinated organic sulfonic acid derivative: trifluoromethanesulfonic acid, trifluoromethylbenzenesulfonic acid, fluorobenzenesulfonic acid (monofluorobenzenesulfonic acid, difluorobenzenesulfonic acid, trifluorobenzenesulfonic acid), fluorosulfonic acid, perfluoroalkyl sulfonic acid compounds (perfluorobutane sulfonic acid, perfluoropentane sulfonic acid, perfluorohexane sulfonic acid, perfluoroheptane sulfonic acid, perfluorononane sulfonic acid, perfluorodecane sulfonic acid, perfluorooctane sulfonic acid).

[0018] Preferably, the concentration of the aqueous solution of the organic ligand in the step (4) is 0.1-0.5 M.

[0019] The present invention also provides an aluminum current collector prepared by the above preparation method.

[0020] The present invention also provides a battery electrode which uses the aforementioned aluminum current collector.

[0021] The present invention also provides a sodium metal battery without a negative electrode which uses the aforementioned electrode.

[0022] Compared with the prior art, the present invention uses a fluorosulfonic acid-based organic ligand as a modification solution to prepare an aluminum negative electrode current collector that can uniformly induce sodium metal deposition. The preparation method of the present invention does not involve complex reaction steps, uses water as the reaction environment, and effectively reduces the preparation cost; the entire treatment process is carried out in the air, and the treatment process is simple and easy to operate. The aluminum foil prepared by the present invention with the function of uniformly inducing sodium metal deposition has a uniform surface under a scanning electron microscope and has more sodium-philic crystal planes. In the actual sodium-free metal battery test, its cycle stability is far superior to that of the untreated commercial aluminum foil (the present invention maintains about 85% of the specific capacity after 200 cycles at a rate of 0.5C, while the commercial aluminum foil rapidly reduces to nearly 0 after only about 50 cycles). The preparation method involved in the present invention is simple and effective, highly operable, and has the potential for popularization and large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described below with reference to the drawings and embodiments.

[0024] Figure 1 (a) is the SEM image of the commercial aluminum foil in Comparative Example 1, and (b) is the SEM image of the trifluoromethanesulfonic acid-modified aluminum foil prepared in Example 1.

[0025] Figure 2 It is the X-ray diffraction pattern of the trifluoromethanesulfonic acid-modified aluminum foil prepared in Example 1.

[0026] Figure 3 It is the long-term cycling performance diagram of the sodium-free metal negative electrode prepared by matching the trifluoromethanesulfonic acid-modified aluminum foil prepared in Example 1 with a sodium vanadium phosphate positive electrode. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0027] The technical solutions of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0028] In all the following embodiments, the aluminum foil used is a single-sided smooth aluminum foil with a thickness of 16 microns produced by Kolude Company.

[0029] Example 1:

[0030] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then, place the dried aluminum foil in a porcelain boat, put it into a tube furnace, heat it to 600 °C at a rate of 10 °C / min in an air atmosphere, keep it for 10 mins, and then naturally cool it to room temperature to obtain uniformly oxidized aluminum foil.

[0031] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.15 M NaOH aqueous solution.

[0032] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 40 °C for 1 min, then take it out and rinse it three times with deionized water.

[0033] (4) Put the sample in step (3) into a 0.5 M aqueous solution of trifluoromethanesulfonic acid, heat it in a water bath at 40 °C for 1 h, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0034] Example 2:

[0035] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, heat it to 400 °C at a rate of 15 °C / min in an air atmosphere, keep it for 30 mins, and then naturally cool it to room temperature to obtain uniformly oxidized aluminum foil.

[0036] (2) Weigh 2 g of sodium carbonate pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.05 M sodium carbonate aqueous solution.

[0037] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 50 °C for 5 mins, then take it out and rinse it three times with deionized water.

[0038] (4) Put the sample in step (3) into a 0.1 M aqueous solution of fluorosulfonic acid, heat it in a water bath at 50 °C for 3 h, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic ligand.

[0039] Example 3:

[0040] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, heat it to 550 °C at a rate of 5 °C / min in an air atmosphere, keep it for 20 mins, and then naturally cool it to room temperature to obtain uniformly oxidized aluminum foil.

[0041] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M NaOH aqueous solution.

[0042] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 30 °C for 3 mins, then take it out and rinse it three times with deionized water.

[0043] (4) Put the sample in step (3) into an aqueous solution of 0.3 M monofluorobenzenesulfonic acid, heat it in a water bath at 45 °C for 2 h, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0044] Example 4:

[0045] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, heat it to 400 °C at a rate of 5 °C / min in an air atmosphere, keep it for 15 mins, and then naturally cool it to room temperature to obtain uniformly oxidized aluminum foil.

[0046] (2) Prepare 0.1 M aqueous ammonia solution.

[0047] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 45 °C for 5 mins, then take it out and rinse it three times with deionized water.

[0048] (4) Put the sample in step (3) into an aqueous solution of 0.2 M difluorobenzenesulfonic acid, heat it in a water bath at 40 °C for 2 h, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0049] Example 5:

[0050] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, heat it to 250 °C at a rate of 5 °C / min in an air atmosphere, keep it for 15 mins, and then naturally cool it to room temperature to obtain uniformly oxidized aluminum foil.

[0051] (2) Weigh 2 g of sodium bicarbonate particles into a beaker, add deionized water and stir until dissolved to obtain 0.3 M aqueous sodium bicarbonate solution.

[0052] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it for 5 mins, then take it out and rinse it three times with deionized water.

[0053] (4) Put the sample in step (3) into an aqueous solution of 0.2 M trifluorobenzenesulfonic acid, heat it in a water bath at 50 °C for 1.5 h, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0054] Example 6:

[0055] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, and heat it to 150 °C at a rate of 5 °C / min in an air atmosphere, hold for 20 mins, and then naturally cool to room temperature to obtain uniformly oxidized aluminum foil.

[0056] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M NaOH aqueous solution.

[0057] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 30 °C for 3 mins, then take it out and rinse it three times with deionized water.

[0058] (4) Put the sample in step (3) into a 0.2 M perfluoropentanesulfonic acid aqueous solution, heat it in a water bath at 45 °C for 2 h, then take it out and cool to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0059] Example 7:

[0060] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, and heat it to 300 °C at a rate of 5 °C / min in an air atmosphere, hold for 20 mins, and then naturally cool to room temperature to obtain uniformly oxidized aluminum foil.

[0061] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M NaOH aqueous solution.

[0062] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 30 °C for 3 mins, then take it out and rinse it three times with deionized water.

[0063] (4) Put the sample in step (3) into a 0.2 M perfluorobutanesulfonic acid aqueous solution, heat it in a water bath at 45 °C for 2 h, then take it out and cool to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0064] Example 8:

[0065] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, and heat it to 350 °C at a rate of 5 °C / min in an air atmosphere, hold for 20 mins, and then naturally cool to room temperature to obtain uniformly oxidized aluminum foil.

[0066] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M NaOH aqueous solution.

[0067] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 30 °C for 3 minutes, then take it out and rinse it three times with deionized water.

[0068] (4) Put the sample in step (3) into an aqueous solution of 0.4 M perfluoropentanesulfonic acid, heat it in a water bath at 50 °C for 2 hours, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0069] Example 9:

[0070] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, heat it to 150 °C at a rate of 5 °C / min in an air atmosphere, keep it for 20 minutes, and then naturally cool it to room temperature to obtain uniformly oxidized aluminum foil.

[0071] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M aqueous NaOH solution.

[0072] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 30 °C for 3 minutes, then take it out and rinse it three times with deionized water.

[0073] (4) Put the sample in step (3) into an aqueous solution of 0.4 M perfluorohexanesulfonic acid, heat it in a water bath at 50 °C for 2 hours, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0074] Example 10:

[0075] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, heat it to 400 °C at a rate of 5 °C / min in an air atmosphere, keep it for 20 minutes, and then naturally cool it to room temperature to obtain uniformly oxidized aluminum foil.

[0076] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M aqueous NaOH solution.

[0077] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 40 °C for 2 minutes, then take it out and rinse it three times with deionized water.

[0078] (4) Put the sample in step (3) into an aqueous solution of 0.3 M perfluorononanesulfonic acid, heat it in a water bath at 55 °C for 1.5 h, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0079] Example 11:

[0080] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, heat it to 150 °C at a rate of 5 °C / min in an air atmosphere, keep it for 20 mins, and then naturally cool it to room temperature to obtain uniformly oxidized aluminum foil.

[0081] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M aqueous NaOH solution.

[0082] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 40 °C for 2 mins, then take it out and rinse it three times with deionized water.

[0083] (4) Put the sample in step (3) into an aqueous solution of 0.3 M perfluoroheptanesulfonic acid, heat it in a water bath at 55 °C for 1.5 h, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0084] Example 12:

[0085] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, heat it to 450 °C at a rate of 10 °C / min in an air atmosphere, keep it for 20 mins, and then naturally cool it to room temperature to obtain uniformly oxidized aluminum foil.

[0086] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M aqueous NaOH solution.

[0087] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 40 °C for 2 mins, then take it out and rinse it three times with deionized water.

[0088] (4) Put the sample in step (3) into an aqueous solution of 0.3 M perfluorodecanesulfonic acid, heat it in a water bath at 60 °C for 1 h, then take it out and cool it to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0089] Example 13:

[0090] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, and heat it to 300 °C at a rate of 5 °C / min in an air atmosphere, hold for 20 mins, and then naturally cool to room temperature to obtain uniformly oxidized aluminum foil.

[0091] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M NaOH aqueous solution.

[0092] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 40 °C for 2 mins, then take it out and rinse it three times with deionized water.

[0093] (4) Put the sample in step (3) into a 0.25 M perfluorooctanesulfonic acid aqueous solution, heat it in a water bath at 40 °C for 1.5 h, then take it out and cool to room temperature, rinse it three times with deionized water and dry it to obtain an aluminum current collector modified with an organic acid ligand.

[0094] Example 14:

[0095] (1) Cut 5 g of aluminum foil and ultrasonically wash it with deionized water and absolute ethanol for 30 s respectively. Then place the dried aluminum foil in a porcelain boat, put it into a tube furnace, and heat it to 600 °C at a rate of 5 °C / min in an air atmosphere, hold for 20 mins, and then naturally cool to room temperature to obtain uniformly oxidized aluminum foil.

[0096] (2) Weigh 2 g of NaOH pellets into a beaker, add deionized water and stir until dissolved to obtain a 0.1 M NaOH aqueous solution.

[0097] (3) Add the sample obtained in step (1) to the solution obtained in step (2), soak it in a water bath at 40 °C for 2 mins, then take it out and rinse it three times with deionized water.

[0098] (4) Put the sample in step (3) into a 0.1 M trifluoromethanesulfonic acid aqueous solution, heat it in a water bath at 60 °C for 1 h, then take it out and cool to room temperature, rinse it three times with deionized water and dry it to obtain a trifluoromethanesulfonic acid modified aluminum current collector.

[0099] Comparative Example 1:

[0100] The commercial copper foil is a single-sided polished aluminum foil with a thickness of 16 microns produced by Kelude Company.

[0101] Perform a sodium-free metal negative electrode battery cycle test on the aluminum foils in Example 1 and Comparative Example 1, and the specific test conditions are as follows.

[0102] 1. Preparation of sodium vanadium phosphate (NVP) cathode: Weigh 0.8 g of NVP powder, 0.1 g of Super-P, and 2 g of a 5% PVDF-NMP solution, add 1 mL of NMP solvent, and ball-mill for 6 hours at a rotation speed of 350 r / min to prepare the cathode slurry. Use a coater to evenly coat the slurry on carbon-coated aluminum foil, place it in a blast drying oven at 80 °C for 2 hours, and then transfer it to a vacuum drying oven at 100 °C for 12 hours. Cut the dried electrode sheet into circular pieces with a diameter of 1.2 cm and weigh the electrode sheet for later use.

[0103] 2. Test of sodium metal battery without anode: Use the aluminum foil of Comparative Example 1 or the trifluoromethanesulfonic acid-modified aluminum foil of Example 1 as the anode and NVP as the cathode.

[0104] 3. Assemble an Al|NVP battery using a NaPF6-Diglyme electrolyte and test the electrochemical performance of the battery at a 0.5C rate of charge and discharge.

[0105] Characterize and analyze the trifluoromethanesulfonic acid-modified aluminum foil current collector prepared in Example 1. Figure 1 This is its scanning electron microscope image. It can be seen that the surface of the aluminum foil is smooth and more uniform. It is speculated that after treatment with trifluoromethanesulfonic acid, the original rough surface of the aluminum current collector is etched. Figure 2 This is its XRD diffraction pattern. The diffraction peak of the (200) crystal plane in this sample is significantly enhanced. The position of the diffraction peak coincides with aluminum PDF#85-1327, representing an increase in the sodium-metal-philic crystal plane on the surface of the aluminum current collector (Tang, F., Yang, Y., Liu, C. et al. Nat Commun 16, 2280 (2025)). Figure 3 This is the electrochemical performance of the trifluoromethanesulfonic acid-modified aluminum foil prepared in Example 1 and the commercial aluminum foil of Comparative Example 1 after matching with NVP to prepare an AL|NVP battery and stably cycling at a 0.5C rate. It can be seen that the interface and cycling stability of this sample are better than those of the commercial aluminum foil, that is, it shows that the electrochemical stability of the trifluoromethanesulfonic acid-modified aluminum foil is better than that of the commercial aluminum foil. After 200 cycles of testing, the capacity of the commercial Al current collector decays rapidly, while the capacity retention rate of the sodium metal-free battery matched with the trifluoromethanesulfonic acid-modified aluminum foil is as high as 85%. The specific capacity of the commercial aluminum foil drops rapidly to a non-detectable level after only about 50 cycles.

[0106] As mentioned above, only the preferred embodiments of the present invention are described. Therefore, the scope of implementation of the present invention cannot be limited thereby. That is, equivalent changes and modifications made according to the scope of the present invention patent and the content of the specification should still fall within the scope covered by the present invention.

Claims

1. A preparation method of an aluminum current collector for a sodium metal battery without a negative electrode, comprising the following steps: (1) Cleaning the aluminum foil in water and ethanol solution respectively to obtain a sample A with a clean surface; (2) Annealing the sample A to obtain a sample B with a sodium-philic metal-rich crystal plane and a uniformly oxidized surface; (3) Treating the sample B with a pre-treatment surface passivation solution to obtain a sample C; (4) Placing the sample C in an aqueous solution containing a fluorosulfonic acid-based organic ligand, and obtaining a surface-modified aluminum current collector containing an anion of the fluorosulfonic acid-based organic ligand through a water bath treatment; the concentration of the fluorosulfonic acid-based organic ligand solution is 0.1 - 0.5 M; the temperature of the water bath treatment is 40 - 60 °C, and the treatment time is 1 - 3 h.

2. According to the preparation method described in claim 1, characterized in that, In step (1), the aluminum foil is at least one of commercial aluminum foils for batteries including single-sided polished aluminum foil, double-sided polished aluminum foil, and microporous aluminum foil.

3. According to the preparation method described in claim 1, characterized in that, In step (2), the annealing temperature is 100 - 600 °C; the annealing time is 10 - 60 mins.

4. According to the preparation method described in claim 1, characterized in that, In step (2), the heating rate of the aluminum foil from room temperature to 100 - 600 °C is 2 - 15 °C / min; the cooling from 100 - 600 °C to room temperature is natural cooling.

5. According to the preparation method described in claim 1, characterized in that, In step (3), the pre-treatment passivation solution is one of sodium hydroxide aqueous solution, ammonia water, sodium carbonate aqueous solution, and sodium bicarbonate aqueous solution; the concentration is 0.05 - 0.5 M; the treatment time is 30 s - 10 mins.

6. According to the preparation method described in claim 1, characterized in that, In step (4): The aqueous solution containing the fluorosulfonic acid-based organic ligand includes at least one of trifluoromethanesulfonic acid, trifluoromethylbenzenesulfonic acid, fluorobenzenesulfonic acid, fluorosulfonic acid, and perfluoroalkylsulfonic acid compounds.

7. According to the preparation method described in claim 6, characterized in that, The fluorobenzenesulfonic acid includes at least one of monofluorobenzenesulfonic acid, difluorobenzenesulfonic acid, and trifluorobenzenesulfonic acid; the perfluoroalkylsulfonic acid compounds include at least one of perfluorobutanesulfonic acid, perfluoropentanesulfonic acid, perfluorohexanesulfonic acid, perfluoroheptanesulfonic acid, perfluorononanesulfonic acid, perfluorodecanesulfonic acid, and perfluorooctanesulfonic acid.

8. An aluminum current collector for a sodium metal battery without a negative electrode, prepared by the preparation method according to any one of claims 1 - 7.

9. A battery electrode, characterized in that, Including the aluminum current collector according to claim 8.

10. A battery, characterized in that, Including the battery electrode according to claim 9.

Citation Information

Cited By

  • Ionic expansive soil modified diaphragm as well as preparation method and application thereof

    CN121149604A